1991
DOI: 10.1002/1097-0142(19911115)68:10<2217::aid-cncr2820681021>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal dysplasia of the liver and the intraductal variant of peripheral cholangiocarcinoma in hepatholithiasis

Abstract: Four cases are reported of the intraductal variant of peripheral cholangiocarcinoma among surgical specimens from 32 cases of hepatolithiasis. The cancers arose from the periphery of the stone‐containing bile duct and spread chiefly along the luminal surface. Microscopically, these tumors showed papillary proliferation and therefore were diagnosed as the intraductal spreading type of peripheral cholangiocarcinoma. Mucosal dysplasia also was noticed in the vicinity of the tumors. In six other cases, mucosal dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 11 publications
(2 reference statements)
1
31
1
Order By: Relevance
“…Chronic biliary infection or stasis, regardless of the presence of hepatolithiasis, has been considered to be a contributing factor in the development of mucosal adenomatous epithelial hyperplasia and bile duct carcinoma. 19,20 In this study, adenomatous hyperplasia was found in all pathological specimens.…”
Section: Discussionmentioning
confidence: 53%
“…Chronic biliary infection or stasis, regardless of the presence of hepatolithiasis, has been considered to be a contributing factor in the development of mucosal adenomatous epithelial hyperplasia and bile duct carcinoma. 19,20 In this study, adenomatous hyperplasia was found in all pathological specimens.…”
Section: Discussionmentioning
confidence: 53%
“…Chronic biliary infection or stasis, regardless of the under- (56,84) have hypothesized that the lining epithelium of the bile duct, when persistently exposed to biochemically altered bile, may undergo a carcinomatous transformation through the stages of mucosal adenomatous hyperplasia and dysplasia. Recurrent pyogenic cholangitis (also called Oriental cholangiohepatitis or intrahepatic pigmented-stone disease), which is also endemic in the Far East, is associated with cholangiocarcinoma in 5 to 10% of cases (9,81).…”
Section: Etiologymentioning
confidence: 99%
“…In 1956, Hou speculated that some carcinogenic substance might act synergistically with C. sinensis to induce cholangio- (84) hypothesized that the lining epithelium of the bile duct, when persistently exposed to chemically altered bile, may undergo a carcinomatous transformation through a stage of mucosal dysplasia. While these propositions seem plausible, it now appears that exogenous environmental carcinogens, which are ubiquitous in nature, are more important.…”
Section: Exogenous and Endogenous Chemical Carcinogensmentioning
confidence: 99%
“…6,11 To date, the histogenesis, histopathology, and early and advanced lesions of this tumor have not been explored in detail.…”
mentioning
confidence: 99%